Flexible heat pump integration to improve sustainable transition toward 4th generation district heating. (1st December 2020) - Abokersh, Mohamed Hany; Saikia, Kangkana; Cabeza, Luisa F.; Boer, Dieter; Vallès, Manel
Graphical abstract: Highlights: Framework to judge transition toward 4th generation district heating is proposed. Multi-objective optimization for evaluating heat pump effect is projected. Various control strategies for the heat pump operation are investigated. Stakeholder perspective is examined using KPIs of 4th generation district heating. Heat pump integration in district heating is a sustainable and competitive solution. Abstract: The movement toward the 4th generation district heating (4GDH) embraces a great opportunity to support the future smart energy development concept. However, its development calls for addressing technological and economic obstacles aligning with the need for a reformation of the energy market to ensure the quality of service. In this context, our paper presents a comprehensive analysis based on a multi-objective optimization framework incorporating an artificial neural network-based model for the possibility of integrating heat pump (HP) into solar assisted district heating system (SDHS) with seasonal thermal energy storage to support the sustainable transition toward 4GDH. The study evaluates the performance of the proposed system with the help of key performance indicators (KPI) related to the 4GDH characteristics and key stakeholders for possible market growth with consideration for the environmental benefits. The proposed analysis is applied to a small neighbourhood of 10 residential buildings located in Madrid (Spain) to investigate the optimal integration of HP under different control strategies into a SDHS. Inherent the SDHS operator perspective, the results reveal a significant improvement in the stabilization of the SDHS performance due to the HP integration where the solar field temperature never exceeds 80 °C, and the seasonal storage tank (SST) temperature stands at 85.4 °C. In addition, the share of solar energy stands above 86.1% with an efficiency of 73.9% for the SST, while the seasonal HP performance factor stands above 5.5 for all optimal scenarios. From the investor viewpoint, an energy price of 59.1 Euro/MWh can be achieved for the proposed system with a payback period of 26 years. Finally, from the policymaker perspective, along with the significant economic and sustainable improvement in the SDHS performance, a substantial environmental improvement of 82.5% is achieved when compared to the conventional boiler heating system. The proposed analysis reflects a great motivation for different stakeholders to propose this system as a path toward the 4GDH in the future district energy systems.